Jaminan Perlindungan Hukum terhadap Terperiksa/Tersangka dari Intimidasi dan Penyiksaan dalam Proses Penyidikan - Rasdiyanah Rasdiyanah; Aftar Akbar; Aulia Ramadhani (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
This study addresses the persistent problem of intimidation and torture during criminal investigations, which undermines human dignity, the presumption of innocence, and the right to a fair trial. Despite existing legal safeguards, such practices continue to occur, indicating a gap between normative regulations and law enforcement practices. This research aims to identify the factors contributing to coercive interrogation methods and to formulate an accountable, human rights-based examination model. The study employs a normative juridical method using statutory, conceptual, and case approaches, supported by primary legal materials and relevant case analyses. The findings reveal that coercion is driven by confession-oriented investigative culture, unequal power relations, limited early access to legal counsel, lack of objective documentation, closed interrogation settings, and weak external oversight. To address these issues, this study proposes an integrated examination model based on five principles: recording, rights protection, rapport-based interviewing, review mechanisms, and effective remedies. This model is expected to prevent false confessions, strengthen evidentiary reliability, and enhance accountability in criminal investigations.